'He called me out of the blue': An ethnographic exploration of contrasting temporalities in a social prescribing intervention. Issue 7 (24th May 2022) - Gibson, Kate; Moffatt, Suzanne; Pollard, Tessa M.
Abstract: Social prescribing, a way of connecting patients to local services, is central to the NHS Personalised Care agenda. This paper employs ethnographic data, generated with 19 participants between November 2018 and July 2020, to explore the socio‐temporal relations shaping their experiences of a local social prescribing intervention. Our focus is on the ways in which the intervention synchronised with the multitude of shifting, complex and often contradictory 'timespaces' of our participants. Our focus on the temporal rhythms of everyday practice allows us to trace a tension between the linearity and long horizon of the intervention and the oft contrasting timeframes of participants, sometimes leading to a mismatch that limited the intervention's impact. Further, we observed an interventional 'drift' from continuity towards unsupported signposting and 'out‐of‐the‐blue' contacts which favour the temporality of the intervention. We demonstrate a need for intervention planning to be flexible to multiple, often conflicting, temporalities. We argue that health interventions must account for the temporal relations lived by the people they seek to support.